2013
DOI: 10.1007/s11255-013-0482-3
|View full text |Cite
|
Sign up to set email alerts
|

Validity of malnutrition scores for predicting mortality in chronic hemodialysis patients

Abstract: The scoring system proposed by the ISRNM most accurately identifies patients at higher risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
0
15
0
3
Order By: Relevance
“…Additionally, malnutrition is associated with low quality of life (physical and mental components) (13). Considering its influence on the immune system, infection control is considered as an important risk factor for prolonged side effects (14), clinical complications (11), and increased mortality in HD patients (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, malnutrition is associated with low quality of life (physical and mental components) (13). Considering its influence on the immune system, infection control is considered as an important risk factor for prolonged side effects (14), clinical complications (11), and increased mortality in HD patients (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the Portuguese Society of Nephrology revealed that, in Portugal, the global mortality rate of patients undergoing haemodialysis (HD) in 2015 was 13.3%. Given the increased nutritional needs of patients undergoing HD compared with the general population and due to several other factors such as increased catabolism, metabolic acidosis, nutrient loses during dialysis, infection and other comorbidities (Molfino et al , Kalantar‐Zadeh & Ikizler ), malnutrition and inflammation are common in these patients and have been associated with adverse clinical outcomes, increased morbidity, mortality and also higher healthcare costs (Correia et al ; Toledo et al ; Rosenberger et al ; Segall et al ). The importance of clinical assessment with regular measures of laboratory and anthropometric parameters has been highlighted as an important way to diagnose malnutrition, inflammation and mortality risk in these patients (Markaki et al ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several anthropometric and laboratory measurements associated with nutritional status, though no single one provides a complete and unequivocal evaluation. Anthropometric parameters such as body mass index (BMI) and also laboratory parameters such as normalised protein catabolic rate (nPCR) and phosphorus are often used as nutritional markers in these patients (Mcquillan et al ; Garagarza et al ; Toledo et al , Segall et al ). BMI is a simple, inexpensive and non‐invasive measure of estimating body mass.…”
Section: Introductionmentioning
confidence: 99%
“…4,11 In 2008, the International Society of Renal Nutrition and Metabolism (ISRNM) recommended its diagnostic criteria for PEW 1 ; however, clinical studies using these criteria are still scarce. [12][13][14] Currently, ISRNM considers that there is no consensus about the relationship of SGA and MIS to the diagnosis of PEW. These scoring systems should be considered as potential clinical markers of PEW status but not as definitive diagnostic indicators of this syndrome.…”
mentioning
confidence: 99%